Joyride : a memoir - Orlean, Susan (Avid Reader Press, 2025)
Joyride is a magic carpet ride through Orlean's life and career, where every day is an opportunity for discovery and every moment holds the potential for wonder. Throughout her storied career, her curiosity draws her to explore the most ordinary and extraordinary of places, from going deep inside the head of a regular ten-year-old boy for a legendary profile ("The American Man Age Ten") to reporting on a woman who owns twenty-seven tigers, from capturing the routine magic of Saturday night to climbing Mt. Fuji. Not only does Orlean's account of a writing life offer a trove of indispensable gleanings for writers, it's also an essential and practical guide to embracing any creative path. She takes us through her process of dreaming up ideas, managing deadlines, connecting with sources, chasing every possible lead, confronting writer's block and self-doubt, and crafting the perfect lede -- a Susan specialty. While Orlean has always written her way into other people's lives in order to understand the human experience, Joyride is her most personal book ever -- a searching journey through finding her feet as a journalist, recovering from the excruciating collapse of her first marriage, falling head-over-heels in love again, becoming a mother while mourning the decline of her own mother, sojourning to Hollywood for films based on her work including Adaptation and Blue Crush, and confronting mortality. Joyride is also a time machine to a bygone era of journalism, from Orlean's bright start in the golden age of alt-weeklies to her career-making days working alongside icons such as Robert Gottlieb, Tina Brown, David Remnick, Anna Wintour, Sonny Mehta, and Jonathan Karp -- forces who shaped the media industry as we know it today. --